Genome-wide identification of three-amino-acid-loop-extension gene family and their expression profile under hormone and abiotic stress treatments during stem development of Prunus mume - Yang, Qingqing; Yuan, Cunquan; Cong, Tianci; Wang, Jia; Zhang, Qixiang (Frontiers in Plant Science, 2022)
Transcription factors encoded by the TALE gene family play a key role in regulating plant growth and development, and are involved in plant hormone regulatory pathways and responses to various environmental stresses. Researchers are currently studying TALE genes in different species, but Prunus mume TALE genes have not yet been studied. Threfore, based on the P. mume genome, we found a total of 23 TALE gene family members, which were distributed on 8 chromosomes. TALE genes contained the characteristic domains of this family, and could be divided into KNOX subfamily and BELL subfamily. They can form heterodimers with each other. Fragment duplication and tandem duplication events were the main reasons for the expansion of P. mume TALE gene family members and the TALE genes were selected by different degrees of purification. The inter-species collinearity analysis showed that the relationship between P. mume and other four Prunus species was consistent with the distance of origin. Eleven members of P. mume TALE genes were specifically highly expressed in stem, mainly at the early stage of stem development. The cis-element analysis showed that the promoter of P. mume TALE genes contained a variety of hormone and abiotic stress response elements, and four TALE genes responded to two kinds of abiotic stresses and four kinds of hormones at the early stage of stem development. In conclusion, this study lays a foundation to explore the roleof TALE gene family in P. mume growth and development.